Theological Values in Inter-religious Relation Verses : A Study on Tafsir Marah Labid - Ainul Yaqin, Muhammad; Saiful Mujab, Muhammad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
Building interreligious relations was often viewed merely from social perspectives. It actually contains theological values. This research attempts to analyze the theological values in the tolerance and interreligious relation verses of the Qur’an that are interpreted by Syaikh Nawawi Al-Bantani. This descriptive-analytical study employs thematic methods by Al-Farmawi. The collected data are then analyzed in terms of its theological aspect. Marah Al-Labid is chosen for it’s written by an Indonesian scholar connecting classic and modern era. In addition, Marah Al-Labid is of Sufistic tafsir. Therefore, it is interesting to know how an Indonesian scholar viewed interreligious relation and its spiritual and theological values in the context of Indonesia. It can be concluded that having interreligious relation is lawful. Muslims are allowed to have social relation with Ahlul kitab or the people of books such as to get marry with them, to eat the meat of the animals they (Jews and Christians) slaughtered, and to have debate and discussion with them in the best way.